Regulatory T Cells Beyond Autoimmunity: From Pregnancy to Cancer and Cardiovascular Disease - Martini, Elisa; Giugliano, Silvia; Rescigno, Maria; Kallikourdis, Marinos (Frontiers in Immunology, 2020)
The evolution of the full range of functions of regulatory T cells (Treg) coincides with the evolution of mammalian pregnancy. Accordingly, Treg function has been shown to be crucial for maternal-fetal tolerance and implantation. As reproduction is a key point of selective pressure, mammalian pregnancy may represent an evolutionary driver for the development of Treg. Yet beyond the chronological boundaries of mammalian pregnancy, several key physiological and pathological events are being gradually uncovered as involving the immunomodulating functions of Treg cells. These include autoimmunity, age-related inflammation in males and in post-menopausal females, but also oncological and cardiovascular diseases. The latter two sets of diseases collectively compose the main causes of mortality world-wide. Emerging data point to Treg-modulable effects in these diseases, in a departure from the relatively narrower perceived role of Treg as master regulators of autoimmunity. Yet recent evidence also suggests that changes in intestinal microbiota can affect the above pathological conditions. This is likely due to the finding that, whilst the presence and maintenance of intestinal microbiota requires active immune tolerance, mediated by Treg, the existence of microbiota per se profoundly affects the polarization, stability, and balance of pro- and anti-inflammatory T cell populations, including Treg and induced Treg cells. The study of these “novel”, but possibly highly relevant from an ontogenesis perspective, facets of Treg function may hold great potential for our understanding of the mechanisms underlying human disease.